Chronic effect of fatmax training on body weight, fat mass and cardiorespiratory fitness in obese subjects: a meta-analysis of randomized clinical trials - Chávez-Guevara, Isaac A.; Urquidez Romero, Rene; Ramos Jimenez, Arnulfo; Pérez-Leon, JorgeAlberto; González-Rodríguez, Everardo; Moreno-Brito, Verónica (2020)
Abstract: Exercise training performed at the maximal fat oxidation intensity (FMT) stands out as a potential treatment of overweight and obesity. This work is a meta-analysis of randomized clinical trials of studies about the efect of FMT on fat mass and maximal oxygen consumption using PubMed, SCOPUS, EBSCOhost, and ScienceDirect as databases. Two independent reviewers selected 11 trials from 356 publications identified by the following keywords: fatmax, lipoxmax, maximal fat oxidation, peak of fat oxidation, physical training, physical exercise, body fat (BF), fat mass, overweight, and obesity. The risk of bias was assessed following the Cochrane Guidelines. The pooled mean diference was computed for each outcome with the random-efects model and the inverse-variance method. The meta-analysis was performed with the RevMan software v 5.3, and the heterogeneity across studies by the I2. The statistical significance was accepted at p < 0.05. Results showed that the FMT reduced body weight (MD = 4.30 kg, p < 0.01, I2 = 0%), fat mass (MD = 4.03 kg, p < 0.01, I2 = 0%), and waist circumference (MD = 3.34 cm, p < 0.01). Fat-free mass remains unchanged (MD = 0.08 kg, p = 0.85), but maximal oxygen consumption increased (MD = 2.96 mL kg 1 min 1, p < 0.01, I2 = 0%). We conclude that FMT at short and medium-term (eight to twenty weeks) reduces body weight and BF, increasing cardiovascular fitness in low physical fitness people with obesity.